Parathyroid carcinoma associated with chronic renal failure and previous radiotherapy to the neck. Issue 10 (October 1985) - Ireland, J P; Fleming, S J; Levison, D A; Cattell, W R; Baker, L R
Abstract : Carcinoma of the larynx was treated by irradiation followed by laryngectomy in a man who had been receiving regular haemodialysis for two years. At least one, and probably two, parathyroid glands were removed at this time, and the remaining two were removed three years later for tertiary hyperparathyroidism. A portion of one gland was implanted into the forearm. The forearm implant was resected the following year for recurrent hypercalcaemia. Six years later, again with recurrent hypercalcaemia, he died of bronchopneumonia. Metastatic parathyroid carcinoma was found in the apex of the left lung. The source of this parathyroid tissue and the possible role of irradiation in the pathogenesis of parathyroid cancer in this patient were investigated.